Interdependent Cultural and Postcolonial Readings of Violence in Chinua Achebe’s Things Fall Apart - Doni Efrizah; Purwarno Purwarno; Indah Sari; Nurbaiti Ali; Eka Surya Fitriani (Balai Bahasa Provinsi Bali, 2026)
Existing scholarship on Things Fall Apart tends to examine indigenous and colonial forms of violence as separate analytical domains, leaving their interconnections underexplored. This study aims to analyze how domestic, ritual, ideological, and structural forms of violence operate as an interdependent system within the novel. Employing a descriptive–interpretive qualitative approach, the study draws on 42 purposively selected textual excerpts from the 2000 edition of the novel. Data were collected through textual documentation and analyzed using close reading and thematic coding informed by postcolonial and gender theory. The findings reveal that violence in the novel operates as a recursive and multi-layered system. Internally sanctioned forms of violence, particularly patriarchal control and culturally legitimized practices, sustain social order while simultaneously generating structural vulnerabilities. These vulnerabilities are subsequently exploited by colonial forces through ideological delegitimization and institutional domination, indicating a shift from physical toward epistemic and symbolic forms of violence. Acts of resistance, although grounded in indigenous moral logic, produce ambivalent outcomes by restoring symbolic authority while provoking intensified repression. These results demonstrate that violence in Things Fall Apart functions as a cyclical and mutually reinforcing process across personal, cultural, and political domains. The study contributes by offering an integrated analytical framework that bridges postcolonial and gender perspectives, while highlighting the novel’s relevance for understanding cultural resilience, identity reconstruction, and the ethical complexities of resistance in postcolonial contexts. Abstrak Kajian-kajian sebelumnya pada Things Fall Apart cenderung meneliti bentuk-bentuk kekerasan pribumi dan kolonial sebagai domain analitis yang terpisah, sehingga keterkaitannya kurang dieksplorasi. Studi ini bertujuan untuk menganalisis bagaimana bentuk-bentuk kekerasan domestik, ritual, ideologis, dan struktural beroperasi sebagai sistem yang saling bergantung dalam novel tersebut. Dengan menggunakan pendekatan kualitatif deskriptif-interpretatif, studi ini mengambil 42 kutipan teks yang dipilih secara purposif dari edisi novel tahun 2000. Data dikumpulkan melalui dokumentasi tekstual dan dianalisis menggunakan pembacaan cermat dan pengkodean tematik yang didasarkan pada teori pascakolonial dan gender. Temuan menunjukkan bahwa kekerasan dalam novel beroperasi sebagai sistem rekursif dan berlapis-lapis. Bentuk-bentuk kekerasan yang disetujui secara internal, khususnya kontrol patriarki dan praktik-praktik yang dilegitimasi secara budaya, mempertahankan tatanan sosial sekaligus menghasilkan kerentanan struktural. Kerentanan ini kemudian dieksploitasi oleh kekuatan kolonial melalui delegitimasi ideologis dan dominasi institusional, yang menunjukkan pergeseran dari bentuk kekerasan fisik menuju bentuk kekerasan epistemik dan simbolik. Tindakan perlawanan, meskipun berlandaskan logika moral pribumi, menghasilkan hasil yang ambivalen dengan memulihkan otoritas simbolik sekaligus memicu represi yang lebih intensif. Hasil ini menunjukkan bahwa kekerasan dalam Things Fall Apart berfungsi sebagai proses siklik dan saling memperkuat di berbagai domain pribadi, budaya, dan politik. Studi ini berkontribusi dengan menawarkan kerangka analitis terintegrasi yang menjembatani perspektif pascakolonial dan gender, sekaligus menyoroti relevansi novel ini untuk memahami ketahanan budaya, rekonstruksi identitas, dan kompleksitas etika perlawanan dalam konteks pascakolonial.